The Effect of the Literacy-Based Learning Model on Reading Ability in Grade III Students of MIS Shafiratunisa - Adinda Dwika; Sahkholid Nasution; Pangulu Abdul Karim (Educare: Journal Educational and Multimedia, 2026)
This research is motivated by the low reading ability of third grade students of MIS Shafiratunnisa in understanding the content of reading, identifying important information, and concluding texts, as well as the dominance of conventional methods in the learning process. This study aims to determine students' reading abilities before and after the implementation of the Literacy-Based Learning model and prove its effect on improving students' reading abilities. This study uses a quantitative approach with a One Group Pretest-Posttest Design. The research subjects. A total of 15 students were selected through a total sampling technique. The research instrument was in the form of 10 essay questions that had been validated by material experts. Data were analyzed using the Paired Sample T Test with the help of SPSS 25. The results showed an increase in the average value from 64.00 in the pretest to 80.33 in the posttest, with a difference in increase of 16.33 points. The data were declared normally distributed based on the Shapiro-Wilk test (Sig. pretest = 0.109; Sig. posttest = 0.190). The results of the Paired Sample T-Test showed a Sig. (2-tailed) = 0.000 < 0.05, so H₀ is rejected and Hₐaccepted. It was concluded that the Literacy-Based Learning model had a significant effect on the reading ability of third-grade students at MIS Shafiratunnisa.